2012
DOI: 10.1159/000341182
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Measurements Underestimate Nocturnal Oxygen Desaturations in Pulmonary Arterial and Chronic Thromboembolic Pulmonary Hypertension

Abstract: Background: Nocturnal hypoxemia is important in precapillary pulmonary hypertension (pPH) as it worsens pulmonary hemodynamics. Whether daytime oxygen saturation (Spo2) predicts nocturnal hypoxemia in pPH patients has not been conclusively studied. Objectives: To investigate the prevalence of nocturnal hypoxemia in comparison to daytime Spo2 and disease severity in ambulatory patients with pulmonary hypertension. Methods: Consecutive patients diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
34
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 65 publications
3
34
1
2
Order By: Relevance
“…This underscores the severe activity limitation in the everyday life of patients affected by pulmonary arterial or chronic thromoembolic PH [13]. In line with previous studies, more than a third of our patients had sleep-disordered breathing with mainly central apnoea/Cheyne-Stokes respiration and low nocturnal oxygen saturation [14,36,37]. However, these disturbances did not result in a subjectively perceived excessive daytime sleepiness.…”
Section: Discussionsupporting
confidence: 88%
“…This underscores the severe activity limitation in the everyday life of patients affected by pulmonary arterial or chronic thromoembolic PH [13]. In line with previous studies, more than a third of our patients had sleep-disordered breathing with mainly central apnoea/Cheyne-Stokes respiration and low nocturnal oxygen saturation [14,36,37]. However, these disturbances did not result in a subjectively perceived excessive daytime sleepiness.…”
Section: Discussionsupporting
confidence: 88%
“…[1][2][3] SDB is relevant because it impairs quality of life. 2 Oxygen deprivation in pulmonary vascular cells during SDB further triggers pulmonary vasoconstriction with increase in pulmonary vascular resistance maintaining a vicious cycle.…”
mentioning
confidence: 99%
“…2 Oxygen deprivation in pulmonary vascular cells during SDB further triggers pulmonary vasoconstriction with increase in pulmonary vascular resistance maintaining a vicious cycle. 3,4 Remodeling of the right ventricle (RV) in response to increased aft erload together with hypoxemia and consecutive myocardial ischemia may aff ect myocardial autonomic activity, lead to conduction and repolarization abnormalities, and represent an arrhythmogenic substrate. 5-7 Cardiac arrhythmias are important infl uencing factors to morbidity and mortality in patients with pulmonary hypertension (PH) and result in clinical deterioration and compromised cardiac function.…”
mentioning
confidence: 99%
“…We and others have demonstrated that SDB including nocturnal oxygen desaturation and periodic breathing are highly prevalent in patients with right heart failure due to PH of various etiologies and are associated with reduced quality of life, impaired exercise capacity, and hemodynamics ( 3 , 34 – 36 ): 39% of 43 PH patients studied at our center had ≥ 10 events/h of Cheyne–Stokes respiration/central sleep apnea (CSR/CSA), and the majority of them (68%) spent more than 10% of the night time with a low arterial SpO 2 (<90%). With the current study, we have shown that SDB in PH are even more pronounced at altitude.…”
Section: Discussionmentioning
confidence: 99%